Elucidating organ-specific metabolic toxicity chemistry from electrochemiluminescent enzyme/DNA arrays and bioreactor bead-LC-MS/MS1. Issue 4 (16th April 2015) - Wasalathanthri, Dhanuka P.; Li, Dandan; Song, Donghui; Zheng, Zhifang; Choudhary, Dharamainder; Jansson, Ingela; Lu, Xiuling; Schenkman, John B.; Rusling, James F.
<x xml:space="preserve">Abstract</x> Combining electrochemiluminescent array and bioreactor bead-LC-MS/MS featuring metabolic enzyme-DNA films provide an efficient, comprehensive approach to simultaneously elucidate metabolic DNA damage chemistries at different human organs for potential new drugs.